Speech coding with traveling wave delays: Desynchronizing cochlear implant frequency bands with cochlea-like group delays - Taft, D.A.; Grayden, D.B.; Burkitt, A.N. (Speech communication, 2009)
Traveling wave delays are the frequency-dependent delays for sounds along the cochlear partition. In this study, a set of suitable delays was calibrated to cochlear implant users’ pitch perception along the implanted electrode array. These delays were then explicitly coded in a cochlear implant speech processing strategy as frequency specific group delays. The envelopes of low frequency filter bands were delayed relative to high frequencies, with amplitude and fine structure unmodified. Incorporating such delays into subjects’ own processing strategies in this way produced a significant improvement in speech perception scores in noise. A subsequent investigation indicated that perceptual sensitivity to changes in delay size was low and so accurate delay calibration may not be necessary. It is proposed that contention between broadband envelope cues is reduced when frequency bands are de-synchronized.